Triarylmethane dye decolorization by pellets of pycnoporus sanguineus: statistical optimization and effects of novel impeller geometry - Sulaiman, S.S.; Annuar, M.S.M.; Abdul Razak, N.N.; Ibrahim, S.; Bakar, B. (2013)
A study was carried out to optimize selected parameters for decolorization of a triarylmethane dye, such as crystal violet by white rot fungus, Pycnoporus sanguineus, pellets. The parameters studied were initial dye concentration (ppm), agitation speed (rpm), and process time (days) and were optimized using response surface methodology (RSM). It is shown that process time, agitation speed, and their interactions have significant effects on the decolorization process. Following the optimization, the decolorization study was extended to a stirred tank reactor (STR) process. Effects of different geometry of impellers on the decolorization process and power consumption were studied. Novel impeller geometries, such as 180° curved blade and 60°angled blade impellers, were used in the STR. The application of 180°curved blade impeller resulted in higher percentage of decolorization at a relatively less power consumption as compared with 60°angled blade impeller. © 2013 Copyright Taylor and Francis Group, LLC.